Cartografias da Alegria na Clínica e na Literatura. - Almeida, Bruno Vasconcelos de (2005)
The present work seeks to englobe Joy in a clinical situation and in literature. In its writing we sought to reconstruct fragments of clinical cases presented throughout a decade in several places and institutions. It has also sought to redeem a series of literary fragments, which in this way or the other, has maintained a curious proximity to the cases mentioned. The dissertation reveals this same joy, in the clinic and in critique, in four specific lines of work which compose a unique architectural structure. In the first one, there is a relation with the intensive that transforms a clinic in a space for the metamorphosis of sensations into intense vibrations. In the second one, joy appears situated in its relation to time and duration. However, in the third line of work, joy is formulated as strength and the expression of this same strength. And, in the last one we show how pain and suffering constitutes a plan conducive to joy, albeit, pain and suffering as material in a clinic, however accosted of this perspective. The conceptual research carried out in an attempt to deal with the problems was made from the encounter with the thoughts of several authors, especially Nietzsche, Espinosa and Blanchot, and mainly Gilles Deleuze and Félix Guattari. The strategy used consisted of the minute research into clinical cases and literary short stories, the elaboration of a thought surrounding the theme joy and the careful note-taking of concepts with the persistent concern about the writing and the actual production of the paper. Concerning the procedures involved in the elaboration of the dissertation, a procedure that contemplates its own ethics, we reassure it was done with utmost joy.